The physiology of rowing with perspective on training and health - Volianitis, S.; Yoshiga, C. C.; Secher, N. H. (European Journal of Applied Physiology, 2020)
Purpose: This review presents a perspective on the expansive literature on rowing. Methods: The PubMed database was searched for the most relevant literature, while some information was obtained from books. Results: Following the life span of former rowers paved the way to advocate exercise for health promotion. Rowing involves almost all muscles during the stroke and competition requires a large oxygen uptake, which is challenged by the pulmonary diffusion capacity and restriction in blood flow to the muscles. Unique training adaptations allow for simultaneous engagement of the legs in the relatively slow movement of the rowing stroke that, therefore, involves primarily slow-twitch muscle fibres. Like other sport activities, rowing is associated with adaptation not only of the heart, including both increased internal diameters and myocardial size, but also skeletal muscles with hypertrophy of especially slow-twitch muscle fibres. The high metabolic requirement of intense rowing reduces blood pH and, thereby, arterial oxygen saturation decreases as arterial oxygen tension becomes affected. Conclusion: Competitive rowing challenges most systems in the body including pulmonary function and circulatory control with implication for cerebral blood flow and neuromuscular activation. Thus, the physiology of rowing is complex, but it obviously favours large individuals with arms and legs that allow the development of a long stroke. Present inquiries include the development of an appropriately large cardiac output despite the Valsalva-like manoeuvre associated with the stroke, and the remarkable ability of the brain to maintain motor control and metabolism despite marked reductions in cerebral blood flow and oxygenation.